Photoacoustic microscopy for studying mechano-transduction response in resistance vessels - Juliana Benavides-Lara; Dianicha Santana Nunez; Mohsin Zafar; Janette Garcia Campos; Shuangping Zhao; Yulia A. Komarova; Kamran Avanaki (Photoacoustics)
Cardiovascular diseases are on the rise, presenting a significant global health challenge. The development of methods enabling the detection of alterations in vascular networks is critical for the early diagnosis and treatment of cardiovascular diseases, including peripheral arterial disease, stroke, and hypertension. Here, we use photoacoustic microscopy (PAM), a non-invasive imaging technique, to monitor morphological changes within the skin vessels of chronically hypertensive mice deficient in the mechanosensitive channel Piezo1 in endothelial cells (Piezo1 EC-KO). We show that, compared to control mice (Piezo1 flox/flox), Piezo1 EC-KO mice are characterized by poorer tissue perfusion due to a vasoconstriction of resistance arterioles. We also show the effect of administration of pharmacological agents on vessel vasodilation in the skin of Piezo1-deficient mice and control mice, identifying quantitative differences between the two groups. These results advance our understanding of vascular mechanodynamics and offer potential implications for developing targeted treatments for hypertensive disorders.